Case Report: Severe SIADH and QTc prolongation induced by escitalopram-quetiapine interaction in a CYP2C19 intermediate metabolizer at therapeutic doses - Jiang, Zongchen; Qu, Xiaoyu; Yan, Zimin; Fang, Jungang; Lan, Jin; Zhao, Xin; Qi, Wensheng (Frontiers in Pharmacology, 2026)
Escitalopram is widely regarded as a well-tolerated selective serotonin reuptake inhibitor (SSRI) with a favorable safety profile. However, severe adverse events can occur even at therapeutic doses in susceptible individuals. Here, we report a rare case of simultaneous life-threatening Syndrome of Inappropriate Antidiuretic Hormone secretion (SIADH) and cardiac toxicity induced by standard-dose escitalopram. A 51-year-old female (weight 50 kg) presented with severe fatigue and anorexia. Initial laboratory results revealed profound hyponatremia (116.1 mmol/L). Following sodium supplementation, serum sodium paradoxically decreased to 114.7 mmol/L (“desalination phenomenon”), while urinary sodium excretion was markedly elevated (220 mmol/24 h) alongside significant hypouricemia (76 μmol/L), confirming the diagnosis of SIADH. Concurrently, the patient manifested significant cardiac toxicity, including sinus bradycardia (41–55 bpm) and marked QTc prolongation (570 ms). Pharmacogenetic analysis identified the CYP2C19 *1/*2 genotype (Intermediate Metabolizer). Despite the therapeutic dosage (10 mg/day) and a non-toxic serum concentration (5 ng/mL measured 72 h post-discontinuation), the patient exhibited severe toxicity, likely driven by “phenoconversion” due to low muscle mass and physiological vulnerability, exacerbated by a pharmacodynamic synergism with low-dose quetiapine. Discontinuation of medications and strict fluid management resulted in complete resolution of both hyponatremia and arrhythmia. The causality was assessed as “probable” for both drugs using the Naranjo Algorithm, and the drug-drug interaction was rated as “probable” using the Drug Interaction Probability Scale (DIPS). This case highlights that genotype-phenotype mismatch, combined with pharmacodynamic synergism (escitalopram-quetiapine interaction), can precipitate severe neuro-cardiac toxicity even at therapeutic levels. It underscores that severe neuro-cardiac toxicity can occur even at therapeutic levels due to individual vulnerability. Therefore, routine monitoring of electrolytes and electrocardiograms (ECG) remains indispensable for patient safety, as pharmacogenetic screening and therapeutic drug monitoring may not predict such idiosyncratic reactions in resource-constrained settings.